Penerapan Thermotherapy dan Aromatherapy Lavender terhadap Penurunan Skala Nyeri pada Pasien Sindrom Koroner Akut - Surani, Wahyu; Lesmana, Hendy; Ose, Maria Imaculata; Pujianto, Ahmat; Nugraha, M Akbar (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT Acute Coronary Syndrome consists of a collection of clinical symptoms of myocardial ischemia which is characterized by pain in the chest. One way to manage pain in ACS patients through non-pharmacological measures is by administering thermotherapy and lavender aromatherapy. Thermotherapy is the application of heat to the body to reduce symptoms of acute and chronic pain. Meanwhile Aromatherapy lavender is an essential oil used for aromatherapy with the main components being linalool and linalic acetate oil. The design of this scientific work uses a case study design conducted on 3 respondents with acute coronary syndrome who experienced chest pain. The instruments in this research were an observation sheet, SOP for administering thermotherapy and lavender aromatherapy, and a measurement sheet using the Numeric Rating Scale. Intervention is carried out twice every 12 hours, once every 24 hours. The results showed that there was a significant change in the pain scale between before the intervention was given and after the intervention was given, where after being given a combination of thermotherapy and lavender aromatherapy intervention, the pain felt by the respondents decreased. The conclusion of this study is that the application of thermotherapy and lavender aromatherapy is effective in reducing the pain scale in patients with acute coronary syndrome. Keywords: Acute Pain, Aromatherapy, Thermotherapy  ABSTRAK Sindrom Koroner Akut terdiri dari kumpulan gejala klinis iskemia miokard yang ditandai dengan adanya rasa nyeri di bagian dada. Salah satu penatalaksanaan nyeri pada pasien SKA melalui tindakan non farmakologi adalah dengan pemberian thermotherapy dan aromatherapy lavender. Thermotherapy merupakan pemberian aplikasi panas pada tubuh untuk mengurangi gejala nyeri akut maupun kronis. Sedangkan Aromatherapy lavender adalah minyak esensial yang digunakan untuk aromaterapi dengan komponen utama minyak linalool dan linalik asetat. Rancangan karya ilmiah ini menggunakan desain studi kasus yang dilakukan pada 3 responden dengan sindrom koroner akut yang mengalami nyeri dada. Instrumen dalam penelitian ini adalah lembar observasi, SOP pemberian thermotherapy dan aromatherapy lavender, dan lembar pengukuran menggunakan Numeric Rating Scale. Intervensi dilakukan sebanyak 2 kali setiap 12 jam sekali dalam 24 jam. Hasil menunjukkan bahwa adanya perubahan skala nyeri yang cukup signifikan antara sebelum diberikan intervensi dan setelah diberikan intervensi, dimana setelah diberikan intervensi kombinasi thermotherapy dan aromatherapy lavender, nyeri yang dirasakan oleh responden berkurang. Kesimpulan dalam penelitian ini adalah penerapan thermotherapy dan aromatherapy lavender efektif dalam menurunkan skala nyeri pada pasien sindrom koroner akut. Kata Kunci: Aromatherapy, Nyeri Akut, Thermotherapy